Prevalence and Risk Factors of Sinus and Nasal Allergies among Tannery Workers of Kanpur City - Gyan Chandra Kashyap; Deepanjali Vishwakarma; Shri Kant Singh (Sinusitis, 2021)
India is greatly afflicted by sinusitis, which is a condition that involves inflaming sinuses (the air cavities in the nasal passage) in your nose, according to the National Institute of Allergy and Infectious Diseases (NIAID). The study’s objective was to evaluate the prevalence and risk factors of sinus and nasal allergies among tannery workers of Kanpur city. The study has used primary datasets obtained from a cross-sectional household study of tannery workers from the Jajmau area of Kanpur in northern India, which was conducted during January–June 2015 as part of a doctoral program. The study covered 286 tannery workers from the study area. Bivariate and logistic regression analysis was used to study the association between outcome variables (self-reported prevalence of sinus and nasal allergies) and predictor variables (socioeconomic and work-related characteristics). Results portray that a higher proportion of the tannery workers belong to economically and socially backward classes. Overall, 13.4 and 12.3% of sinus and nasal allergy prevalence have been reported by tannery workers, whereas tannery workers from the oldest age group were those who mainly suffered. A study found that the severity of nasal and sinus allergies increases with the increasing age and work duration in the tannery. Workers with low exposure to airborne dust were significantly more likely to develop sinus problems (OR = 4.16; p < 0.05) than those without exposure. Those tannery workers suffering from nasal allergy were more prone to develop sinus problems than those who were not suffering from nasal allergy. The risk factors responsible for these health hazards can be eliminated by improving the overall working conditions and ensuring necessary protective regulations for the tannery workers.